Pemanfaatan Internet Sebagai Media Pembelajaran Di Sd Negeri 1 Sindurejo Kecamatan Toroh Kabupaten Grobogan - , Suwarti; , Prof. Dr. Bambang Sumardjoko; , Dr. Sabar Narimo, M.M., M.Pd (2016)
ABSTRACT Suwarti.Q.100.140.073. Use of the Internet as a medium of learning in SD Negeri 1 Grobogan Toroh Sindurejo districts. Thesis. Graduate Muhammadiyah University of Surakarta. 2016. The purpose of this research is to describe (1) The role of teachers in the use of the Internet as a medium of learning. (2) Constraints faced by teachers in the use of the Internet as a medium pembelajara. (3) Expectations desirable from stickholder with the use of the Internet as a medium of learning. Research methods. The research is a qualitative or naturalistic. Who is the subject of research is the principal, teachers and students of SD Negeri 1 Sindurejo. Data collection techniques using observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulation sources. The results of this study were (1) The role of teachers is needed as the spearhead in the control and delivery of content to be taught. Use of the Internet as a medium of learning has been applied to almost all existing matapelajaran, with perencanakan into lesson plans, instructional media that are used in the form of pictures or video obtained from mensin google search. (2) Obstacles Internet utilization is the level of understanding and mastery of the internet from every teacher is different, their internet network interruption. The existence of a power outage. (3) The Internet is expected to provide support for the implementation of the learning process more qualified and qualified. Although internet-based learning media applied SD Negeri 1 Sindurejo, the teacher's role in providing guidance, direction, empathy to students remain and will not be replaced by any media. Internet functions only as learning activities that support learning objectives can achieve maximum results. Internet use in the learning activities in addition to being one of the innovations in the field of education that adapts to the progress of time, as well as through the internet more wide open horizons of knowledge and science without borders. With the Internet as a medium of learning expected of teachers and students Internet technology literate, able to use Internet applications related to learning, able to add insight in various matters related to learning. Teachers will be more creative in giving assignments through interactive media, namely the Internet. Keywords : internet, media, learning